My pilgrimage to the spirit - Patel, Govindbhai, 1906- (Grace Infinite Foundation Trust : sole distributor, Patel, 1977)
Spiritual experiments of a follower of Aurobindo Ghose, 1872-1950 and La Mère, 1878-1973.